Meta-Study Analysis of the Effectiveness of Intermittent Fasting as Insomnia Therapy - Rainhard, Octovianto; Maja, Pertiwi; Seilly, Jehosua (Eduvest - Journal of Universal Studies, 2025)
Circadian rhythm disturbances can lead to disruptions in the wake-sleep cycle, resulting in insomnia. Leptin and ghrelin, digestive hormones secreted by the stomach, influence the gut-brain axis. Leptin secretion affects the ventral hypothalamus, reducing metabolism and increasing melatonin secretion, which is essential for initiating sleep. Intermittent fasting (IF) is known to improve circadian rhythms and elevate leptin levels. This study involved a literature search from databases like PubMed, Google Scholar, and ScienceDirect, guided by PRISMA, including five studies. Meta-analysis of the relationship between IF and total sleep time showed a positive effect with heterogeneous data (WMD 2.1; -0.05, 0.81), while the 8-hour eating window subgroup showed no significant change (WMD 3.5; 2.89, 4.11). Analysis of IF and the Insomnia Sleep Index (ISI) revealed a positive effect (WMD 0.58; 0.17, 1.00), with no significant improvement in the 6-month subgroup (WMD 0.96; 0.54, 1.38). The relationship between IF and the Pittsburgh Sleep Quality Index (PSQI) initially showed negative effects (WMD -0.06; -0.41, 0.29), but after six months, it showed positive effects (WMD 0.61; 0.23, 0.98). These results suggest IF benefits sleep quality, but larger, longer studies are needed for better outcomes.